The Effectiveness of Al-Miftah Lil Ulum in Learning the Yellow Book in the Intensive Course of Pare Kediri - Ahmad Saeful Ahyar; Syarif Maulidi; Memed Khumaedi (Edumaspul: Jurnal Pendidikan, 2026)
The ability to read the yellow book is still an important competency in Islamic education, but many students experience difficulties due to the weak mastery of Arabic rules, especially in the context of non-formal education. This study aims to analyze the effectiveness of the Al-Miftah Lil Ulum method in learning the yellow book in the Al-Azhar Pare Kediri Arab Village Advanced Book Program (Maktab). The research uses a descriptive qualitative approach with a field research design. Data were obtained through participatory observation of around ten meetings, in-depth interviews with three teachers and five students who were selected purposively, and documentation analysis. Data analysis was carried out using the Miles and Huberman model through data reduction, data presentation, and conclusion drawn, while the validity of the data was strengthened through triangulation of sources and methods. The results of the study show that the Al-Miftah Lil Ulum method is effective in improving the ability to read the yellow book through four main aspects, namely increasing the mastery of nahwu-sharaf, the ability to read the yellow book, motivation and learning engagement, and the success of applying the method to participants with heterogeneous backgrounds. The novelty of this research lies in the finding that the Al-Miftah Lil Ulum method, which has been widely studied in the formal pesantren environment, is also effectively applied to non-formal Arabic language courses that are intensive. Theoretically, these findings expand the understanding of the adaptability of the yellow book learning method outside the context of Islamic boarding schools. Practically and policyly, the results of this research can be a reference for the development of yellow book literacy programs in non-formal Islamic educational institutions. Abstrak Kemampuan membaca kitab kuning masih menjadi kompetensi penting dalam pendidikan Islam, namun banyak peserta didik mengalami kesulitan akibat lemahnya penguasaan kaidah bahasa Arab, terutama pada konteks pendidikan nonformal. Penelitian ini bertujuan menganalisis efektivitas metode Al-Miftah Lil Ulum dalam pembelajaran kitab kuning pada Program Mahir Kitab (Maktab) Kampung Arab Al-Azhar Pare Kediri. Penelitian menggunakan pendekatan kualitatif deskriptif dengan desain penelitian lapangan. Data diperoleh melalui observasi partisipatif sekitar sepuluh kali pertemuan, wawancara mendalam dengan tiga pengajar dan lima santri yang dipilih secara purposive, serta analisis dokumentasi. Analisis data dilakukan menggunakan model Miles dan Huberman melalui reduksi data, penyajian data, dan penarikan kesimpulan, sedangkan keabsahan data diperkuat melalui triangulasi sumber dan metode. Hasil penelitian menunjukkan bahwa metode Al-Miftah Lil Ulum efektif meningkatkan kemampuan membaca kitab kuning melalui empat aspek utama, yaitu peningkatan penguasaan nahwu-sharaf, kemampuan membaca kitab kuning, motivasi dan keterlibatan belajar, serta keberhasilan penerapan metode pada peserta dengan latar belakang yang heterogen. Kebaruan penelitian ini terletak pada temuan bahwa metode Al-Miftah Lil Ulum yang selama ini banyak dikaji pada lingkungan pesantren formal juga efektif diterapkan pada lembaga kursus bahasa Arab nonformal yang bersifat intensif. Secara teoretis, temuan ini memperluas pemahaman mengenai adaptabilitas metode pembelajaran kitab kuning di luar konteks pesantren. Secara praktis dan kebijakan, hasil penelitian ini dapat menjadi rujukan bagi pengembangan program literasi kitab kuning pada lembaga pendidikan Islam nonformal.